Academic Self-Efficacy Profile of Fifth-Semester Students - Awalya Siska Pratiwi; Abel Embun Bunga Salsabila (Asosiasi Asesmen Pendidikan (AAP), 2026)
The stages of learning development in students are complex internal experiences, not merely a matter of scores or academic achievement, but also require individuals to manage their belief in their own potential. One psychological aspect that plays a role in supporting student academic success is self-efficacy, which is an individual's belief in their capacity to complete a learning task or specific job optimally. This study uses a quantitative approach with a descriptive method. The population consisted of all fifth-semester students in one class at Universitas Negeri Malang, with a total of 30 students selected through total sampling. The population consisted of all fifth-semester students in one class at Universitas Negeri Malang, with 30 students selected through total sampling. The research instrument was a Self-Efficacy Scale registered under Intellectual Property Rights (HKI), comprising 21 items on a Likert scale and the reliability through Cronbach's alpha (α = 0.898). The results show that 53% of fifth-semester students fall in the high self-efficacy category and 47% in the moderate category, with no students in the low category. These findings suggest that most students have a good level of academic self-confidence in facing academic tasks, shaped by accumulated learning experiences across previous semesters. Several factors thought to influence self-efficacy include mastery experience, vicarious experience, verbal persuasion, and psychological states.